Tissue factor as a potential coagulative/vascular marker in relapsing-remitting multiple sclerosis - Koudriavtseva, Tatiana; Lorenzano, Svetlana; Cellerino, Maria; Truglio, Mauro; Fiorelli, Marco; Lapucci, Caterina; D’Agosto, Giovanna; Conti, Laura; Stefanile, Annunziata; Zannino, Silvana; Filippi, Maria Maddalena; Cortese, Antonio; et al. (Frontiers in Immunology, 2023)
Objectives: Recent studies supported coagulation involvement in multiple sclerosis, an inflammatory-demyelinating and degenerative disease of the central nervous system. The main objectives of this observational study were to identify the most specific pro-coagulative/vascular factors for multiple sclerosis pathogenesis and to correlate them with brain hemodynamic abnormalities. Methods: We compared i) serum/plasma levels of complement(C)/coagulation/vascular factors, viral/microbiological assays, fat-soluble vitamins and lymphocyte count among people with multiple sclerosis sampled in a clinical remission (n=30; 23F/7M, 40±8.14 years) or a relapse (n=30; 24F/6M, age 41±10.74 years) and age/sex-matched controls (n=30; 23F/7M, 40±8.38 years); ii) brain hemodynamic metrics at dynamic susceptibility contrast-enhanced 3T-MRI during relapse and remission, and iii) laboratory data with MRI perfusion metrics and clinical features of people with multiple sclerosis. Two models by Partial Least Squares Discriminant Analysis were performed using two groups as input: (1) multiple sclerosis vs. controls, and (2) relapsing vs. remitting multiple sclerosis. Results: Compared to controls, multiple sclerosis patients had a higher Body-Mass-Index, Protein-C and activated-C9; and a lower activated-C4. Levels of Tissue-Factor, Tie-2 and P-Selectin/CD62P were lower in relapse compared to remission and HC, whereas Angiopoietin-I was higher in relapsing vs. remitting multiple sclerosis. A lower number of total lymphocytes was found in relapsing multiple sclerosis vs. remitting multiple sclerosis and controls. Cerebral-Blood-Volume was lower in normal-appearing white matter and left caudatum while Cerebral-Blood-Flow was inferior in bilateral putamen in relapsing versus remitting multiple sclerosis. The mean-transit-time of gadolinium-enhancing lesions negatively correlated with Tissue-Factor. The top-5 discriminating variables for model (1) were: EBV-EBNA-1 IgG, Body-Mass-Index, Protein-C, activated-C4 and Tissue-Factor whereas for model (2) were: Tissue-Factor, Angiopoietin-I, MCHC, Vitamin A and T-CD3. Conclusion: Tissue-factor was one of the top-5 variables in the models discriminating either multiple sclerosis from controls or multiple sclerosis relapse from remission and correlated with mean-transit-time of gadolinium-enhancing lesions. Tissue-factor appears a promising pro-coagulative/vascular biomarker and a possible therapeutic target in relapsing-remitting multiple sclerosis. Study Registration Information: ClinicalTrials.gov Identifier, NCT04380220, first posted on May 8, 2020) (https://clinicaltrials.gov/ct2/show/NCT04380220). Funding: Italian Ministry of Health (PE-2013-02357745).